2018
DOI: 10.1016/j.asoc.2017.12.045
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid method of 2-TSP and novel learning-based GA for job sequencing and tool switching problem

Abstract: One of the well-known problems in single machine scheduling context is the Job Sequencing and Tool Switching Problem (SSP). The SSP is optimally sequencing a finite set of jobs and loading restricted subset of tools to a magazine with the aim of minimizing the total number of tool switches. It has been proved in the literature that the SSP can be reduced to the Job Sequencing Problem (JSeP). In the JSeP, the number of tool switches from the currently processed job to the next job depends on the sequencing of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 40 publications
(106 reference statements)
0
30
0
1
Order By: Relevance
“…Additionally, the use of a heuristic approach to solve the job sequencing and tool-switching problem (SSP) has been reported in Paiva and Carvalho (2017). In another study (Ahmadi et al 2018), SSP has been modelled as a secondorder travelling-salesman problem, and the same has been solved using a learning-based GA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the use of a heuristic approach to solve the job sequencing and tool-switching problem (SSP) has been reported in Paiva and Carvalho (2017). In another study (Ahmadi et al 2018), SSP has been modelled as a secondorder travelling-salesman problem, and the same has been solved using a learning-based GA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Population-based methods have also been successful. Hybrid methods combining genetic algorithms (GA) with other search procedures can be found in [2,4,5,6,7,8,18]. Amaya et al [4,6,7] combined GA with local search-based procedures such as hill climbing, simulated annealing and tabu search, leading to hybrid methods which are also known under the name of memetic algorithms.…”
Section: Related Studiesmentioning
confidence: 99%
“…Amaya et al [5,6,8] combined genetic algorithms with a multi-agent approach or cross-entropy methods. Finally, Chaves et al [18] combined clustering search (CS) with a biased random-key genetic algorithm (BRKGA), while Ahmadi et al [2] combined a 2-TSP scheme with a novel learning-based GA. Table 1 summarizes the SSP studies in chronological order, lists their main contributions as well as the origin of the benchmark instances considered.…”
Section: Related Studiesmentioning
confidence: 99%
“…Recently, Ahmadi et al (2018) showed that the SSP can be formulated as a TSP of second order (2-TSP). They present a dynamic Q-learning-based GA that is seeded by the solutions obtained from solving the SSP as 2-TSP.…”
Section: The Uniform Sspmentioning
confidence: 99%